Biological removal of chloroorganics from water and wastewater - Rakmi, Abd-Rahman, Prof. Dr.; Abu Zahrim, Yaser; Azizah, Abu-Bakar (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/